Electronic Land Registration System at the National Land Agency - rokhimatul rokhimatul khasanah (Authentica, 2022)
Lan registration aims to provide legal certainty. National Land Agency as the appointed institution to carry out land registration, has progressed by providing land services and mortgages electronically. This study aims to examine the procedure for registering land with an electronic system at the Land Office and the application of theory/principle of land registration with an electronic system. This research applied normative juridical with a statute approach and case approach. The reference of this study is that the government and land registration organizers, i.e. the Ministry of National Land Agency, should re-evaluate, the completeness and quality of the electronic land registration system. This is done so that users of the electronic registration system feel more benefits and ease in using the service. The government and land registration organizers should also hold socialization of electronic technology training to National Land Agency employees, Land Deed Officials and the community in general. So that in carrying out registration with this electronic system, it can be mastered by users of the electronic system as a whole. Keywords: procedure, land registration, electronics.